2008
DOI: 10.4161/chan.2.1.6051
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of paramyotonia congenita mutations F1473S and F1705I on sodium channel gating

Abstract: We investigated effects of paramyotonia congenita mutations F1473S and F1705I on gating of skeletal muscle Na + channels. We used on-cell recordings from Xenopus oocytes to compare fast inactivation and deactivation in wild-type and mutant channels. Then, we used gating current recordings to determine how these actions of PC mutants might be reflected in their effects on charge movement and its immobilization. F1473S, but not F1705I, accelerated deactivation from the inactivated state and enhanced the remobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
(84 reference statements)
1
7
0
Order By: Relevance
“…I Na decay, particularly at negative voltages, results from both inactivation and deactivation. We found no significant difference in the rates of deactivation at voltages between −180 and −100 mV (p<0.05; Figure S3 in File S1) similar to previous results [33]. However, at voltages from −90 mV to −60 mV, τ Deactivation of hNa V 1.4 F1705I in the Ca 2+ free condition is significantly larger than in the wild type channel, with or without Ca 2+ (p<0.05; Figure S3 in File S1).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…I Na decay, particularly at negative voltages, results from both inactivation and deactivation. We found no significant difference in the rates of deactivation at voltages between −180 and −100 mV (p<0.05; Figure S3 in File S1) similar to previous results [33]. However, at voltages from −90 mV to −60 mV, τ Deactivation of hNa V 1.4 F1705I in the Ca 2+ free condition is significantly larger than in the wild type channel, with or without Ca 2+ (p<0.05; Figure S3 in File S1).…”
Section: Resultssupporting
confidence: 92%
“…Slowing of deactivation of hNa V 1.4 may cause sustained skeletal muscle contraction by delaying repolarization thereby prolonging action potential duration [34]. Differential temperature-induced changes in mutant channel gating; particularly slowing of deactivation resulting in persistent membrane depolarization has been proposed for some hNa V 1.4 mutations causing myotonia [40]; however, the F1705I mutation does not alter deactivation [33]. Additionally, it has been suggested that at normal temperatures more wild type channels are activated compared to mutant channels and with lowering of temperature mutant channels dominate membrane excitability [41].…”
Section: Discussionmentioning
confidence: 99%
“…For some preparations, including the gating currents from squid axon Na + channels, 56 and those from K + channels from Drosophila and rat brain expressed in oocytes, 24,57 the Q OFF failed to quickly recover at the end of a depolarizing pulse, a phenomenon known as charge immobilization. Charge immobilization has been mostly linked to channel entry in an inactivated state, either from the open, 24 or from the closed state (such as in skeletal muscle Na + channels); 58 on the other hand, charge immobilization is absent in the gating currents recorded from channels carrying non-inactivating currents, such as K V 2.1, 25 inactivation removed Shaker B, 59 and EAG channels. 29 In the present experiments, the maximal absolute values of the Q ON and Q OFF gating currents from oocytes expressing K V 7.4 channels were identical, suggesting that charge immobilization did not occur.…”
Section: Resultsmentioning
confidence: 99%
“…For example, mutations in SCN4A, the gene coding for the skeletal muscle sodium channel Na v 1.4, cause paroxysmal muscle dysfunction known as paramyotonia congenita (PMC), an autosomal dominant disorder with cold-and exercise-induced stiffness as well as weakness. [1][2][3][4][5][6][7] Not all SCN4A mutations, however, lead to this phenotype. Of the 66 mutations identified so far (see appendix e-1 on the Neurology ® Web site at www.neurology.org), only half are associated with PMC.…”
mentioning
confidence: 99%